(Trans)missions : monasteries as sites of cultural transfers (2022)
This volume focuses on the Catholic tradition of consecrated life (vita religiosa) from the High Middle Ages to the present. It gathers papers by authors from various disciplinary backgrounds, in particular art history, history, anthropology and translation studies.